ASSESSMENT OF EMPLOYEE PERFORMANCE WITH THE BEHAVIORALLY ANCHORED RATING SCALE (BARS) (JESII: Journal of Elektronik Sistem InformasI, 2023)
PT. JAVFLO CIPTA MANDIRI is a company engaged in the Mechanical-Electrical field and has an office located in Bandung. Currently, the process of evaluating employee performance on Key Performance Indicators is still being done conventionally and using the rating scale method in calculating employee performance appraisals. A rating scale or measurement scale is a tool for collecting data in the form of lists containing characteristics or behaviors that must be recorded in stages to facilitate the selection of research data. Therefore we need a system that can solve these problems. The assessment method used is the Behaviorally Anchored Rating Scale (BARS) to determine the value of employee performance and the application used is SPSS (Statistical Product and Service Solutions). The purpose of this data processing is to determine the value of employee performance with the Behaviorally Anchored Rating Scale method with the SPSS application. The result of this study is the value of employee performance.